Islamic Financial Literacy and Behavioral Gaps in A Rural Agrarian Community - Herlista, He Wa Ode; Syarifuddin, Syarifuddin; Anggrayni, Lilly (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Manado, 2025)
This study aims to comprehensively analyze the level of Islamic financial literacy in the agrarian community in Modayag II Village, East Bolaang Mongondow Regency, to fill the literacy data gap in rural areas of Eastern Indonesia. Adopting a qualitative approach with a case study method through in-depth interview techniques, this study reveals that the dominant community literacy profile is in the Sufficient-Literate category. Field findings show that cognitively and affectively, people have a solid fundamental understanding of the prohibition of usury and have a very positive attitude and religious belief towards the blessings of the Islamic economic system, which is reflected in compliance with paying zakat. However, a significant gap was identified between spiritual intentions and actual economic behavior, where dependence on conventional banking and informal lending was still high due to pragmatism. Through the analysis of the Theory of Planned Behavior (TPB), this study found that the main obstacle is not in the aspect of value or subjective norms, but in the weak behavior control (Perceived Behavioral Control) caused by the deficit in the accessibility of Sharia service infrastructure in rural areas. This study concludes that literacy improvement strategies must shift from normative education to structural interventions in providing physical and digital access, as well as formalizing local social capital to transform literacy awareness into real, sustainable, and economic inclusion of the people.